Comparative sequence analysis of pPATH pathogenicity plasmids in Pantoea agglomerans gall-forming bacteria - Geraffi, Naama; Gupta, Priya; Wagner, Naama; Barash, Isaac; Pupko, Tal; Sessa, Guido (Frontiers in Plant Science, 2023)
Acquisition of the pathogenicity plasmid pPATH that encodes a type III secretion system (T3SS) and effectors (T3Es) has likely led to the transition of a non-pathogenic bacterium into the tumorigenic pathogen Pantoea agglomerans. P. agglomerans pv. gypsophilae (Pag) forms galls on gypsophila (Gypsophila paniculata) and triggers immunity on sugar beet (Beta vulgaris), while P. agglomerans pv. betae (Pab) causes galls on both gypsophila and sugar beet. Draft sequences of the Pag and Pab genomes were previously generated using the MiSeq Illumina technology and used to determine partial T3E inventories of Pab and Pag. Here, we fully assembled the Pab and Pag genomes following sequencing with PacBio technology and carried out a comparative sequence analysis of the Pab and Pag pathogenicity plasmids pPATHpag and pPATHpab. Assembly of Pab and Pag genomes revealed a ~4 Mbp chromosome with a 55% GC content, and three and four plasmids in Pab and Pag, respectively. pPATHpag and pPATHpab share 97% identity within a 74% coverage, and a similar GC content (51%); they are ~156 kb and ~131 kb in size and consist of 198 and 155 coding sequences (CDSs), respectively. In both plasmids, we confirmed the presence of highly similar gene clusters encoding a T3SS, as well as auxin and cytokinins biosynthetic enzymes. Three putative novel T3Es were identified in Pab and one in Pag. Among T3SS-associated proteins encoded by Pag and Pab, we identified two novel chaperons of the ShcV and CesT families that are present in both pathovars with high similarity. We also identified insertion sequences (ISs) and transposons (Tns) that may have contributed to the evolution of the two pathovars. These include seven shared IS elements, and three ISs and two transposons unique to Pab. Finally, comparative sequence analysis revealed plasmid regions and CDSs that are present only in pPATHpab or in pPATHpag. The high similarity and common features of the pPATH plasmids support the hypothesis that the two strains recently evolved into host-specific pathogens.